Ferroelectrics and Their Applications - Irzaman, Husein (IntechOpen, 2018)
Ferroelectricity is a symptom of inevitable electrical polarization changes in materials without external electric field interference. Ferroelectricity is a phenomenon exhibited by crystals with a spontaneous polarization and hysteresis effects associated with dielectric changes when an electric field is given. Our fascination with ferroelectricity is in recognition of a beautiful article by Itskovsky, in which he explains the kinetics of a ferroelectric phase transition in a thin ferroelectric layer (ﬁlm). We have been researching ferroelectric materials since 2001. There are several materials known for their ferroelectric properties. Barium titanate and barium strontium titanate are the most well known. Several others include tantalum oxide, lead zirconium titanate, gallium nitride, lithium tantalate, aluminium, copper oxide, and lithium niobate. There is still a blue ocean of ferroelectric applications yet to be expounded. It is and hopefully always will be a bright future.